Malignant Hyperthermia: Report of Two Cases with a Neglected Complication in Cardiac Surgery - Mahdi Neshati; Manizheh Azadeh; Parinaz Neshati; Tyrone Burnett; Ryan Saenz; Bahman Karbasi; Ghader Shahmohammadi; Eskandar Nourizadeh; Mohsen Rostamzadeh (Journal of Tehran University Heart Center, 2018)
Malignant hyperthermia (MH) can develop after contact with volatile anesthetics (halothane, enflurane, isoflurane, sevoflurane, and desflurane) as well as succinylcholine and cause hypermetabolism during anesthesia, which is associated with high mortality when untreated. Early diagnosis and treatment could be life-saving. During cardiac surgery, hypothermia and cardiopulmonary bypass make the diagnosis of MH extremely challenging compared with other settings such as general surgery.